Algebra 2
posted by Sira .
( ∛3x+5 ) + 4 = 0

third root ( 3 x ) + 5 + 4 = 0
third root ( 3 x ) + 9 = 0
third root ( 3 x ) =  9
93 x =  9 ^ 3
3 x =  729 Divide both sides by 3
x =  729 / 3
x =  243 
If your expression mean :
third root ( 3 x + 5 ) + 4 = 0
then
third root ( 3 x + 5 ) =  4
3 x + 5 =  4 ^ 3
3 x + 5 =  64
3 x =  64  5
3 x =  69 Divide both sides by 3
x =  69 / 3
x =  23
Respond to this Question
Similar Questions

algebra
I am really stuck, can someone please help me with this? 
math
∛(270x )∛(10x^4) subtract by simplifying by collecting like terms 
Math
Multiply and simplify by factoring. Assume that all expressions under radicals represent nonnegative numbers. ∛(y^13 ) ∛(¡¼16y¡½^14 ) Am I supposed to add the exponents and multiply the little 3's? 
Math Reiny?
Multiply and simplify by factoring. Assume that all expressions under radicals represent nonnegative numbers. ∛(y^13 ) ∛(¡¼16y¡½^14 ) I got ∛16y^27 Am I right? 
Please help! MATH
Multiply and simplify by factoring. Assume that all expressions under radicals represent nonnegative numbers. ∛(y^13 ) ∛(¡¼16y¡½^14 ) Am I supposed to add the exponents and multiply the little 3's? 
Math I really need help!
Multiply and simplify by factoring. Assumem that all expressions under radicals represent nonnegative numbers. ∛(y^13) ∛(16y^14) ∛y^13 x 16y^14 ∛16y^27 Am I even close here? 
Math
∛(y^13) ∛(16y^14)Multiply and simplify assume all expressions under radicals represent non negative number My friend helped me she said azanswer is 12(y^13)(square root sybol y) 
algebra 2nd try
I need to simplify this 2/∛49 . I figured it out to be (2∛((49)^2))/49 but the system I added my answer to says this is incorrect. Please help me! Thanks anyone. 
Simplify
Simplify the following number. ∛729 I think it is ∛9, but I do not know. Please help, and check my answer. I will appreciate it if you guys can answer this as soon as possible. It is part of a RATIONAL EXPONENTS question. … 
PreCalculus 11
Simplify the following ∛375/4 This is how far I got ∛5*5*5*3/4